Characterization and Mechanistic Study of the Radical SAM Enzyme ArsS Involved in Arsenosugar Biosynthesis. (25th February 2021) - Cheng, Jinduo; Ji, Wenjuan; Ma, Suze; Ji, Xinjian; Deng, Zixin; Ding, Wei; Zhang, Qi
Abstract: Arsenosugars are a group of arsenic‐containing ribosides that are found predominantly in marine algae but also in terrestrial organisms. It has been proposed that arsenosugar biosynthesis involves a key intermediate 5′‐deoxy‐5′‐dimethylarsinoyl‐adenosine (DDMAA), but how DDMAA is produced remains elusive. Now, we report characterization of ArsS as a DDMAA synthase, which catalyzes a radical S‐adenosylmethionine (SAM)‐mediated alkylation (adenosylation) of dimethylarsenite (DMAs III ) to produce DDMAA. This radical‐mediated reaction is redox neutral, and multiple turnover can be achieved without external reductant. Phylogenomic and biochemical analyses revealed that DDMAA synthases are widespread in distinct bacterial phyla with similar catalytic efficiencies; these enzymes likely originated from cyanobacteria. This study reveals a key step in arsenosugar biosynthesis and also a new paradigm in radical SAM chemistry, highlighting the catalytic diversity of this superfamily of enzymes. Abstract : We report characterization of ArsS as a DDMAA synthase, which catalyzes a radical S‐adenosylmethionine (SAM)‐mediated alkylation (adenosylation) of dimethylarsenite (DMAs III ) to produce DDMAA. This radical‐mediated reaction is redox neutral, and multiple turnover can be achieved without external reductant. This study reveals a key step in arsenosugar biosynthesis and also a new paradigm in radical SAM chemistry.